Gender and HIV testing service uptake: trend in Northern Nigeria (2016)
HIV counseling and testing remains a fundamental entry point of care in limiting transmission of HIV/AIDS. Community outreaches serves the dual function of improving access to service and outcome of care through early linkages and subsequent initiation of Anti-Retroviral Therapy (ART). Gender and socio-cultural factors affects uptake of screening services and ultimately early treatment. This study therefore assessed gender-related HIV counseling and testing uptake and linkage to care among those who were tested. A review of data from 423 community outreaches conducted between August 2012 to July 2015 by AHF Nigeria in which information on socio-demographic characteristics, HIV counseling and testing and time to accessing care was obtained. Means and proportions were used to document the results. With a monthly Mean of 2650 [male 68.8% female 38%] clients counselled, tested and received results, 2.6% (SD 0.7) were positive; male 33.5% (SD 10) female 60.8% (SD 9). An average of 64% of positive clients were linked to care; male 40% (SD 10) female 60% (SD 10). Male predominance in testing uptake with more female positive results and early linkage to care forms a persisting trend. HIV testing activities aimed at increasing female participation by addressing social and cultural barriers limiting their participation through advocacy and community dialogue approaches would increase case detection and early linkages to care and help reduce gaps in prevention and treatment in HIV.